2014
DOI: 10.4049/jimmunol.1302992
|View full text |Cite
|
Sign up to set email alerts
|

Lymphopenia Associated with Highly Virulent H5N1 Virus Infection Due to Plasmacytoid Dendritic Cell–Mediated Apoptosis of T Cells

Abstract: Although lymphopenia is a hallmark of severe infection with highly pathogenic H5N1 and the newly emerged H7N9 influenza viruses in humans, the mechanism(s) by which lethal H5N1 viruses cause lymphopenia in mammalian hosts remains poorly understood. Because influenza-specific T cell responses are initiated in the lung draining lymph nodes, and lymphocytes subsequently traffic to the lungs or peripheral circulation, we compared the immune responses in the lung draining lymph nodes following infection with a leth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 35 publications
2
61
0
Order By: Relevance
“…Additionally, severe respiratory virus infection can induce acute respiratory disease syndrome (ARDS), which is associated with significant epithelial-endothelial dysfunction and excessive activation of macrophages and neutrophils (104). ARDS has been observed during experimental IAV infection of animal models, as well as in people naturally infected with highly pathological IAV isolates, such as the 1918 H1N1 "Spanish" influenza strain and the recent zoonotic outbreaks of avian H5N1 and H7N9 IAV strains (105)(106)(107). An eloquent transcriptome analysis by Josset et al, which compared highly pathological versus seasonal IAV infections, detected a strong transcriptional signature of macrophages and neutrophils in the lungs of mice with severe IAV infection (108), which fits with prior histological observations (16).…”
Section: Role Of Mast Cells In Allergies and Asthmamentioning
confidence: 99%
“…Additionally, severe respiratory virus infection can induce acute respiratory disease syndrome (ARDS), which is associated with significant epithelial-endothelial dysfunction and excessive activation of macrophages and neutrophils (104). ARDS has been observed during experimental IAV infection of animal models, as well as in people naturally infected with highly pathological IAV isolates, such as the 1918 H1N1 "Spanish" influenza strain and the recent zoonotic outbreaks of avian H5N1 and H7N9 IAV strains (105)(106)(107). An eloquent transcriptome analysis by Josset et al, which compared highly pathological versus seasonal IAV infections, detected a strong transcriptional signature of macrophages and neutrophils in the lungs of mice with severe IAV infection (108), which fits with prior histological observations (16).…”
Section: Role Of Mast Cells In Allergies and Asthmamentioning
confidence: 99%
“…One was recovered from a fatal human infection associated with lymphopenia; this virus caused lymphopenia and was lethal for mice. The other virus was isolated from a nonfatal human case without lymphopenia; this virus replicated in the lungs of mice but was not associated with lymphopenia or lethality (32). We found that lethal H5N1 infection enhanced Fas ligand (FasL) expression on plasmacytoid DCs (pDCs), resulting in apoptosis of influenza-specific CD8 + T cells via a Fas-FasL-mediated pathway; this was not seen in mice infected with the nonlethal H5N1 strain (32).…”
Section: Pathogenesis Of Severe Diseasementioning
confidence: 89%
“…31). Infection of DCs by IAVs does not normally result in cell death or productive viral infection, but HP H5N1 avian IAV can cause productive infection and can also kill certain human DC subsets (32,33).…”
Section: The Immune Response To Iavsmentioning
confidence: 99%
“…Lymphopenia was strongly associated with a higher chance of death in our ndings. Previous studies implied that lymphopenia can have a prognostic value in viral infections (51), and a recent study reported that COVID-19 patients with low blood lymphocyte percentages had poor outcomes (5, 52).…”
Section: Laboratory and Radiologic Ndingsmentioning
confidence: 99%